Pengaruh Ketahanan Bisnis, Kompetensi Kewirausahaan Dan Kapabilitas Keuangan Terhadap Kinerja Bisnis UMKM (Studi Keuangan Pada UMKM Nasabah PT FIFGROUP) - Zulaikah, June; Wahono, Budi; Bastomi, Mohamad (UNIVERSITAS ISLAM MALANG, 2024)
AbstractÂ This research aims to analyze the influence of business resilience, entrepreneurial competency and financial capability on business performance in MSME customers of PT FIFGROUP. The population in this research is MSME customers of PT FIFGROUP Malang Raya. The data collection technique uses a non-probability sampling technique, namely the purposive sampling technique. The sample in this study amounted to 103 respondents. The data analysis techniques used are research instrument tests, classical assumption tests, multiple regression analysis tests, coefficient of determination tests, and t tests. The results of this research simultaneously and partially show that Business Resilience, Entrepreneurial Competence and Financial Capability have a significant effect on Business Performance in MSME Customers of PT FIFGROUP.Â Keywords:Â Business Resilience, Entrepreneurial Competence, Financial Capability and Business Performance